2014
DOI: 10.1111/1755-5922.12075
|View full text |Cite
|
Sign up to set email alerts
|

Dipeptidyl Peptidase‐4 Inhibitors and Cardiovascular Outcomes: Meta‐Analysis of Randomized Clinical Trials with 55,141 Participants

Abstract: Aims:The association between glucose lowering in diabetes mellitus and major cardiovascular (CV) outcomes is weak; indeed, some oral hypoglycemic agents are associated with increased CV events. Dipeptidyl peptidase-4 inhibitors (DPP-4 inhibitors) are a new class of oral hypoglycemic agent that may have beneficial CV effects. We undertook a systematic review and meta-analysis to appraise the CV safety and efficacy of DPP-4 inhibitors. Methods: Comprehensive search for prospective trials involving DPP-4 inhibito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
82
1
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(91 citation statements)
references
References 67 publications
3
82
1
5
Order By: Relevance
“…Compared to previous meta-analyses [8,9], our study was larger in size. The studies by Wu et al and Monami et al were conducted with 24 and 37 studies, respectively.…”
Section: Accepted M Manuscriptmentioning
confidence: 64%
See 3 more Smart Citations
“…Compared to previous meta-analyses [8,9], our study was larger in size. The studies by Wu et al and Monami et al were conducted with 24 and 37 studies, respectively.…”
Section: Accepted M Manuscriptmentioning
confidence: 64%
“…However, only 54 studies were included into the data analysis while 4,098 studies were excluded. Reasons for exclusion were irrelevance or failure to meet inclusion/exclusion criteria (4,080), post-hoc analysis in nature (8) and data duplication (10). As a result, a total of 54 studies with 74,737 patients were included in the final analysis (9 with alogliptin [7,[21][22][23][24][25][26] A C C E P T E D M A N U S C R I P T…”
Section: Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Contradicting, several other safety trials have shown that DPP-4i do not increase or decrease major adverse CV events over several years of use in individuals with T2DM and CV diseases [21].…”
Section: Introductionmentioning
confidence: 99%